Is it who you are or what you do? Insights for Mobility as a Service from research on a car club. (December 2021) - Catulli, Maurizio; Potter, Stephen; Cook, Matthew
Abstract: The concept of Mobility as a Service (MaaS) is for a personalised, one-stop travel management platform digitally unifying trip purchase and delivery across all transport modes. MaaS has potential to reduce the environmental impact of personal mobility, yet its implementation has been hindered by challenges including consumer acceptance. There is little research on the issue, particularly in the context of existing MaaS exemplars. This paper draws on insights from research into a related concept, the Product Service System (PSS), which is a resource efficient system of products and services supported by networks and infrastructure. The application of findings from PSS research to MaaS may avoid duplicated efforts and offer a template for further research. The paper draws on two complementary views of PSS consumption, one shaped by consumers' choice and the other by socio-material structures. The findings suggest that whilst consumers may choose to use PSS for mobility because it defines their identities, their consumption through PSS is constrained because they are locked in the geographical configuration of social life. These insights have implications for policies to support MaaS and suggest that whilst a view of consumer choice encourages interventions such as educational communications, socio-material structures inform interventions based on structural investment.